Minutes of the 5th Meeting of BRAC University Board of Trustees, BRACU - Board of Trustees (BoT), BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of the Minutes of the 4th Meeting of the Board of Trustees, BRACU. 2. Review of the progress and implementation of decisions of the 4th Meeting of Board of Trustees, BRACU. 3. Appointment of Pro-Vice Chancellor. 4. Induction of new members in the Board of Trustees. 5. Approval of the Minutes of the 28th Meeting of the Finance Committee held on 28 March 2012. 6. Approval of the Minutes of the 29th Meeting of the Finance Committee held on 7 June 2012 and Annual Budget for Financial Year 2012-2013. 7. Report on progress of Permanent Campus. 8. Briefing by Ms. Susan Davis, President & CEO of BRAC USA. 9. Briefing by Prof. Sohail Inayatullah and his team on 'Future Search' of BRACU. 10. Hiring of Additional Space for BRAC University. 11. Report on the Progress of the 8th Convocation. 12. Report of the 6th Meeting of Syndicate held on 11 June 2012. 13. Report on the 46th Meeting of the Academic Council held on 29 May 2012. 14. Approval of the Appointments made in the Faculty Appointment Committee Meetings held on 8 & 22 March,11 April, and 10 June 2012. 15. Approval of the Appointments made in the Staff Appointment Committee Meetings held on 22 March, and 10 June 2012. 16. Report on the 4th Meeting of the Disciplinary Committee held on 8 March 2012. 17. Report on the 5th Meeting of the Disciplinary Committee held on 16 May 2012. 18. Miscellaneous: 18.1 Appointment of the Treasurer. 18.2 Issues Regarding JPGSPH. 18.3 Development of Strategic Plan for IGS.